2017
DOI: 10.1007/s13187-017-1294-4
|View full text |Cite
|
Sign up to set email alerts
|

Age-Specific Patient Navigation Preferences Among Adolescents and Young Adults with Cancer

Abstract: AYAs with cancer have different preferences for patient navigation by developmental age at diagnosis. AYAs are not a one-size-fits-all population, and navigation programs can better assist AYAs when services are targeted to appropriate developmental ages. Future research should examine fertility and navigation preferences by time since diagnosis. While some navigation needs to span the AYA age range, other needs are specific to developmental age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 24 publications
1
45
0
Order By: Relevance
“…Age may be particularly relevant in determining preferred communication format, as generational preferences for certain types of communication may differ between younger and older AYAs. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Age may be particularly relevant in determining preferred communication format, as generational preferences for certain types of communication may differ between younger and older AYAs. 28 …”
Section: Discussionmentioning
confidence: 99%
“…Shih et al recently recommended that standards of care should include screening for financial toxicity, and that system‐wide approaches should focus on patient‐provider communication regarding the financial impact of cancer, treatment decisions that reflect patients’ values based on evidence, prognosis, and their financial standing, and directing patients at higher risk of financial toxicity for financial assistance programs . Our studies of AYA cancer patients demonstrate that they want to have cost conversations with providers . As AYA oncology programs continue to increase in numbers, they provide an important environment to increase provider awareness of these issues and to develop and test age‐appropriate financial support programs for AYAs with cancer.…”
mentioning
confidence: 86%
“…Qualitative findings from a study that investigated patient‐navigator needs and preferences for AYA patients with cancer during and after treatment highlighted the need for health insurance, child care, and financial support. Differences emerged among the developmental subgroups: adolescents (15–18 years) were interested in educational assistance and information about how health insurance works; emerging adults (19–25 years) and young adults (26–39 years) wanted a review of medical bills, detailed information about health insurance payments, and financial assistance for living expenses; and young adults additionally wanted financial assistance for treatment‐related expenses . A novel pilot feasibility study of a financial navigation program has been reported recently to reduce anxiety about the costs of cancer care in older adult patients with cancer, which could have relevance for AYAs.…”
Section: Addressing Financial Toxicitymentioning
confidence: 99%